Szkotyzm w Polsce - Gensler, Marek; Jung-Palczewska, Elżbieta (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 1998)
During the 15th century the Cracow University had become a major intellectual centre in central Europe. It was especially important in educating lawyers and administrators for the Polish-Lithuanian state as well as the higher clergy: as a result, special stress was put on legal and theological studies. The faculty of Liberal Arts (Philosophy), though less prized, also took part in the intellectual life of the Latin Europe, becoming home to representatives of most philosophical schools of the late Middle Ages. Scotism was one of the last medieval schools to arrive in Cracow. It was introduces there by Michael Twaróg of Biestrzyków, who studied the doctrines of scotism in logic and metaphysics. His main source was not Duns Scotus, however, but his pupils and followers, notably Antonius Andreae, whose "Quaestiones super XII libros Metaphysicae" was a book widely read in Cracow since 1489. Antonius' solutions on the division of sciences, the subject-matter of metaphysics, the concept of being, etc. were accepted also by Nicholas of Michałowice, Martin Kulap of Tarnowiec, John of Głogów, and John of Stobnica. Some of them tried to combine some scotist ideas with philosophical views of other schools. In logic, the solutions associated with scotism started appearing in Cracow s little earlier – in 1470s – but their influence was weaker than in metaphysics. Again, they were mostly coming from the works of Scotus's followers of the 14th and early 15th century. The group of Cracow logicians influences by scotist opinions included John of Głogów, Michael of Wrocław, Nicholas of Giełczewo and Michael od Biestrzyków, who tried to combine the views of Scotus with those of Peter of Spain in his commentary on "Parva naturalia". Philosophy of nature was the discipline in which the influence of scotism was felt last and least. It is found mostly in the works of John of Stobnica – especially in his commentary on "Parvulus philosophiae naturalis" (1498) – and Simon of Leśniewo, John's pupil, who wrote glossa to the commentary.